Learning C# by developing games with Unity : get to grips with coding in C# and build simple 3D games in Unity 2022 from the ground up - Ferrone, Harrison (Expert insight., 2022)
It's the ability to write custom C# scripts for behaviors and game mechanics that really takes Unity the extra mile. That's where this book can help you as a new programmer! Harrison Ferrone, in this seventh edition of the bestselling series, will take you through the building blocks of programming and the C# language from scratch while building a fun and playable game prototype in Unity. This book will teach you the fundamentals of OOPs, basic concepts of C#, and Unity engine with lots of code samples, exercises and tips to go beyond the book with your work. You will write C# scripts for simple game mechanics, perform procedural programming, and add complexity to your games by introducing intelligent enemies and damage-dealing projectiles. You will explore the fundamentals of Unity game development, including game design, lighting basics, player movement, camera controls, collisions, and more with every passing chapter.